Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.5 The Chain Rule - 2.5 Exercises - Page 158: 18



Work Step by Step

$$g'(x)=((x^2+1)^3(x^2+2)^6)'=((x^2+1)^3)'(x^2+2)^6+(x^2+1)^3((x^2+2)^6)'= 3(x^2+1)^2(x^2+1)'(x^2+2)^6+(x^2+1)^36(x^2+2)^5(x^2+2)'= 3(x^2+1)^2\cdot2x(x^2+2)^6+6(x^2+1)^3(x^2+2)^5\cdot2x= 6x(x^2+1)^2(x^2+2)^5(x^2+2+2(x^2+1))= 6x(x^2+1)^2(x^2+2)^5(3x^2+4)$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.